It's all part of the customer journey: the impact of augmented reality, chatbots, and social media on the body image and self-esteem of Generation Z female consumers - Ameen, Nisreen; Jun, Hwa Cheah; Kumar, Satish (Wiley, 2022)
Research is needed to identify novel ways to influence Generation Z female consumers' behavior when they interact with various technologies. This study investigates how experiences of using augmented reality, artificial intelligence-enabled chatbots, and social media when interacting with beauty brands affect body image, self-esteem, and purchase behavior among female consumers in Generation Z. Through three studies, we propose and test a model drawing on social comparison theory. In Study 1, a survey was completed by Generation Z women (n = 1118). In Study 2 and Study 3, two laboratory experiments were conducted with Generation Z women in Malaysia (n = 250 and n = 200). We show that (1) Generation Z women's perceived augmentation positively affects their body image, self-esteem, and actual purchase behavior; (2) although trust in social media celebrities positively affects Generation Z women's body image and self-esteem, the addictive use of social media does not have significant effects; (3) the chatbot support type (assistant vs. friend) has a significant impact on these women's experience; and (4) brand attachment, reputation, and awareness do not have significant effects. This article provides important implications for theory and practice on the behavior of Generation Z females when interacting with various technologies.